1977
DOI: 10.1002/1097-0142(197702)39:2+<751::aid-cncr2820390710>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen in radiation therapy

Abstract: The importance of oxygen with low LET radiations has been established beyond any doubt in many different systems, both plant and animal. While some studies, especially head and neck tumors, are impressive, it has not been demonstrated unequivocally that radiation under hyperbaric conditions is superior to well fractionated, well conceived, conventional radiotherapy. Any resulting gain in survival from the addition of hyperbaric oxygen will be limited, especially with more advanced stages of disease. Well contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…cervix carcinoma (Bergsj0 and Kolstad, 1968;Dische et al, 1983;Revesz and Balmukhanov, 1987;H6ckel et al, 1993), head and neck carcinoma (Glassburn et al, 1977;Henk et al, 1977;Gatenby et al, 1988;Okunieff et al, 1995) and breast carcinoma (Okunieff et al, 1993). Streffer et al (1989) have suggested that hypoxia-induced radiation resistance can be attributed to low vascular density in tumours.…”
mentioning
confidence: 99%
“…cervix carcinoma (Bergsj0 and Kolstad, 1968;Dische et al, 1983;Revesz and Balmukhanov, 1987;H6ckel et al, 1993), head and neck carcinoma (Glassburn et al, 1977;Henk et al, 1977;Gatenby et al, 1988;Okunieff et al, 1995) and breast carcinoma (Okunieff et al, 1993). Streffer et al (1989) have suggested that hypoxia-induced radiation resistance can be attributed to low vascular density in tumours.…”
mentioning
confidence: 99%